Comparison of clinical features in patients with eosinophilic esophagitis living in an urban and rural environment. Issue 1 (1st January 2015) - Lee, Y.-J.; Redd, M.; Bayman, L.; Frederickson, N.; Valestin, J.; Schey, R.
Summary: Eosinophilic esophagitis (EoE) has been associated with exposure to aeroallergens. Living in different locations (urban vs. rural) could potentially expose individuals to different environmental factors. Currently, there is limited data on the matter, and all was based on small population studies that did not exclude proton pump inhibitor (PPI)-responsive esophageal eosinophilia in their cohort. The primary aim of this study was to determine the prevalence of EoE in an urban versus rural population and compare demographic and clinical characteristics in patients that had been treated with high-dose PPI prior to diagnosis. Esophageal biopsies were obtained from a cohort of patients who presented with symptoms of dysphagia, odynophagia, globus sensation, and heartburn during a 10-year period. Only patients who had biopsies from the mid and distal esophagus with ≥20 eosinophils per high-power field while on high-dose PPI treatment during endoscopy were included. Urban population was defined as >1000 people/square mile, and rural population was defined as ≤1000 people/square mile (U.S. Census Bureau). Demographic data from each group was analyzed for age, sex, body mass index, duration of symptoms, and tobacco use. Chi-square analysis was used for frequencies with statistical significance defined as P ≤ 0.05. A total of 20 718 patients were identified and their records evaluated. From this cohort, 57 (0.28%) symptomatic patients (male/female: 39/18, mean age = 29.5 years) had biopsy-proven EoE (≥20 eosinophils/hpf) while on PPI treatment. Of those EoE patients, 29 (50.9%) reported living in rural area versus 28 (49.1%) living in the urban area. The most common medical history components included asthma (12.3%), and the most common presenting symptoms included dysphagia (50.9%), heartburn (26.3%), and nausea/vomiting (22.8%). The average duration of symptoms, body mass index, and smoking habits did not differ between the groups. Dysphagia was significantly more prevalent in the urban population (37.9% vs. 64.3% P = 0.047), while heartburn and reflux were more prevalent in the rural population (37.9% vs. 14.3 P = 0.043). Asthma was prevalent in both populations without a significant difference ( P = not significant). There is no residential variation in the incidence of EoE among patients with non-PPI-responsive esophageal eosinophilia. Dysphagia was more prevalent in the urban population, while heartburn and reflux symptoms were more prevalent in the rural environment. Further exploration of environmental factors and specific allergens may help explain the varying symptoms and causes of EoE.